A Contemporary Overview of PPARα/γ Dual Agonists for the Management of Diabetic Dyslipidemia - Balakumar, Pitchai (Curr Mol Pharmacol, 2019)
BACKGROUND: Diabetes mellitus and concomitant dyslipidemia, being referred to as ‘diabetic dyslipidemia’, are the foremost detrimental factors documented to play a pivotal role in cardiovascular illness. Diabetic dyslipidemia is associated with insulin resistance, high plasma triglyceride levels, low HDL-cholesterol concentration and elevated small dense LDL-cholesterol particles. Maintaining an optimal glucose and lipid levels in patients afflicted with diabetic dyslipidemia could be a major task that might require a well-planned diet-management system and regular physical activity, or otherwise an intake of combined antidiabetic and antihyperlipidemic medications. Synchronized treatment which efficiently controls insulin resistance-associated diabetes mellitus and co-existing dyslipidemia could indeed be a fascinating therapeutic option in the management of diabetic dyslipidemia. Peroxisome proliferator-activated receptors α/γ (PPARα/γ) dual agonists are such kind of drugs which possess therapeutic potentials to treat diabetic dyslipidemia. Nevertheless, PPARα/γ dual agonists like muraglitazar, naveglitazar, tesaglitazar, ragaglitazar and aleglitazar have been reported to have undesirable adverse effects, and their developments have been halted at various stages. On the other hand, a recently introduced PPARα/γ dual agonist, saroglitazar is an emerging therapeutic agent of glitazar class approved in India for the management of diabetic dyslipidemia, and its treatment has been reported to be generally safe and well tolerated. CONCLUSION: Some additional and new compounds, at initial and preclinical stages, have been recently reported to possess PPARα/γ dual agonistic potentials with considerable therapeutic efficacy and reduced adverse profile. This review sheds light on the current status of various PPARα/γ dual agonists for the management of diabetic dyslipidemia.